2011
DOI: 10.1590/s0100-29452011000400001
|View full text |Cite
|
Sign up to set email alerts
|

Controle do crescimento vegetativo e floração de mangueiras cv. Kent com reguladores de crescimento vegetal

Abstract: O paclobutrazol é utilizado para o manejo da produção de manga na maioria dos pomares, com aplicação no solo, o que contribui para a maior persistência no ambiente. Assim, este trabalho teve como objetivo avaliar o efeito de reguladores de crescimento vegetal aplicado via foliar, prohexadione-Ca, etil-trinexapac e cloreto de chlormequat, e via solo, paclobutrazol, no controle da brotação vegetativa e na floração de mangueiras 'Kent'. O experimento foi conduzido na região do Vale do São Francisco, em Petrolina-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Regarding biostimulant effect on panicle length, Mouco et al (2011) evaluated the action of different plant regulators on the vegetative and floral shoots of 'Kent' mango trees cultivated in Petrolina, Brazil, and verified differences for this variable, with results varying from 13.25 to 41.24 cm, a broader range than that found in the present study. According to Husen et al (2012), high PBZ doses applied in mango trees tend to compact the panicles.…”
Section: Discussionsupporting
confidence: 68%
“…Regarding biostimulant effect on panicle length, Mouco et al (2011) evaluated the action of different plant regulators on the vegetative and floral shoots of 'Kent' mango trees cultivated in Petrolina, Brazil, and verified differences for this variable, with results varying from 13.25 to 41.24 cm, a broader range than that found in the present study. According to Husen et al (2012), high PBZ doses applied in mango trees tend to compact the panicles.…”
Section: Discussionsupporting
confidence: 68%
“…In Brazil, previous studies have reported the use of the following gibberellin biosynthesis inhibitors: paclobutrazol (Cardoso et al, 2007;Mouco et al, 2010;Upreti et al, 2013;Chatzivagiannis et al, 2014), uniconazole (Silva et al, 2010), and trinexapac-ethyl in mango (Mangifera indica L.) trees (Mouco et al, 2010(Mouco et al, , 2011(Mouco et al, , 2013; and prohexadione-calcium in apple (Malus domestica Borkh) trees (Hawerroth et al, 2012;Hawerroth & Preti, 2014). However, no studies have been reported on the use of these phytoregulators in nonirrigated avocado trees.…”
Section: Introductionmentioning
confidence: 99%
“…O paclobutrazol (PBZ) é um regulador vegetal do grupo dos triazóis, que atua inibindo a síntese de giberelinas. O bloqueio da síntese de giberelinas resulta na redução do crescimento vegetativo e promove a floração da mangueira (Mouco et al, 2011). O uso do paclobutrazol em mangueiras é bastante difundido nas regiões tropicais, sendo aplicado via solo, geralmente após uma poda (Upreti et al, 2013), uma vez que desempenham importante função na indução floral, permitindo o escalonamento da produção durante o ano e atendendo aos diversos mercados disponíveis.…”
Section: Introductionunclassified